Enhancing ethanol production using a hybrid of firefly algorithm and dynamic flux balance analysis - Leong, Wan Ting, 1990-; Mohd. Saberi Mohamad, supervisor; Fakulti Komputeran (2015)
Project Paper (Sarjana Muda Sains Komputer (Bioinformatik)) - Universiti Teknologi Malaysia, 2015